Evolution of argoma shrubland (Ulex gallii Planch.) after clearing and burning treatments in Sierra de Aralar and Belate (Navarra) - Gómez, D.; Aguirre, A.J.; Lizaur, X.; Lorda, M.; Remón, J.L. (Cuadernos de Investigación Geográfica, 2019)
Shrub encroachment is considered one of the greatest threats in the conservation of pastures, especially in abandoned territories and territories with low stocking density. However, in the Navarra Pyrenees and Basque mountains, with a high stocking density maintained during the last decades, the expansion of argoma shrubland (Ulex gallii), shows that grazing is not enough for its control and requires evaluating measures of clearing. To evaluate the efficiency of the burning and the mechanical clearing (with two treatments: at ground level and 10 cm above ground) in the control of the shrub, these treatments were applied in different plots of encroached grasslands in two pastoral territories (Sierra de Aralar and Belate). After the burning and clearing, the evolution of the shrub was compared in the cleared plots closed to grazing and in their replicas open to it. The results showed differences between the different treatments in both territories that may be related to the initial coverage of the shrubland. In general, burning was less effective in controlling shrubland and allowed a greater resprout than mechanical clearing. No significant differences were found between the two types of mechanical clearing (at ground level and at 10 cm above ground). Finally, grazing caused a delay in the recovery of the shrub in all casesbut it was not able to eliminate the shrubs completely. From the field observations, the opinions of the farmers and the results of similar experiences, some measures for grassland management were collected and discussed to correct or complement the clearing treatments in order to increase their efficiency.